Ketergantungan pada Sektor Minyak dan Gas dalam Pembangunan Timor-Leste: Implikasi terhadap Kemiskinan dan Keberlanjutan Ekonomi - Setiawan, Dwi Desky; Ahmad, Fauzan Ramdani; Athalla, Muhammad Rifqy Addin; Hutasoit, Onma Bryan Yehezkiel; Indrawan, Jerry (Indonesian Democracy Research Center, 2025)
This study aims to examine the effect of Timor-Leste's dependence on the oil and gas sector on national economic growth, poverty distribution, and fiscal sustainability in the long run. Since gaining independence in 2002, Timor-Leste has relied on oil and gas as the main source of Gross Domestic Product (GDP) and state budget funding. Using qualitative methods, this study analyzes the role of the oil and gas sector in the country's economic structure, the efficiency of Petroleum Fund management, and constraints in achieving economic diversification. The findings indicate that heavy dependence on oil and gas has resulted in a situation that is vulnerable to changes in world oil prices, slowed the growth of the non-oil sector, and exacerbated social inequality and poverty. While the Petroleum Fund was created as a tool for sustainable resource management, fiscal practices show disbursements exceeding safe limits, jeopardizing future economic resilience. The study recommends the importance of fiscal policy reform, improved resource management, and a development approach that focuses on economic diversification and social inclusiveness to achieve sustainable development.